(untitled) (International Journal of Banking and Finance, 2023)
In recent years, banks in Nigeria have experienced a significant increase in delinquent loan portfolios, which has contributed immensely to the financial difficulties in this sector. Due to the trust of depositors, banks should be responsible for the efficient utilization of resources to achieve cost efficiency, which in turn contributes to raising income. This paper seeks to investigate the moderating role of the cost per loan asset ratio (CLAR) on the relationship between credit risk and return on asset (ROA) of Nigerian deposit money banks (DMBs). This study employs panel data analysis followed by the use of GLS regression models to examine the relationship in question. The population consists of all fifteen (15) listed DMBs in the Nigerian stock market as at December 31st, 2018, while the adjusted population was eleven (11). The results revealed a significant positive moderating relationship between the non-performing loan ratio (NPLR) and capital adequacy ratio (CAR), while the loan loss provision ratio (LLPR) and asset quality ratio (AQR) were negative, but statistically significant. Moreover, the cost per loan asset ratio was found to have an inverse moderating effect on the relationship between the loan and advance ratio (LADR) and the bank’s probability, even though it was not statistically significant. Based on the research findings, the study recommends that policymakers focus on capital regulation as measured by the capital adequacy ratio, risk level, liquidity, and operational cost efficiency. In addition, banks should have effective and efficient strategies to manage credit risks, which might help to enhance their performance.